Nestle China : working towards sweet success in the chocolate confectionery market. - Loo, Monica WenQi. (2008)
This paper will focus mainly on Nestl?’s operations in China and in particular its participation in the chocolate confectionery market. The purpose of doing this is to look in-depth into the current emerging Chinese economy, and more specifically the current market situation in the chocolate confectionery market.